Development of UI / UX Design in Web-Based Artificial Intelligence Learning on Student Learning Motivation with a User-centered Design Approach - Masyita Insyra Putri; Erna Piantari; Enjun Junaeti (Jurnal Guru Komputer, 2023)
Artificial Intelligence (AI) is a study of intelligent machines. Starting from elementary school, children should have the opportunity to learn computer science, both from computational thinking and programming. Based on that case, an e-learning platform that discusses AI with block-based programming was created, namely eCraft2Learn. Based on the results of field studies, the measurement of user experience and user interface shows the "bad" category on each scale. Whereas in e-learning, UI/UX is the point of interaction as the key in achieving educational goals. It is necessary to develop UI/UX both in terms of structure and content presentation, collaboration, and interaction so that it can influence student learning and motivation. Thus, the UI/UX development is carried out by applying the four stages of the user-centered design method. After all stages of the method are carried out, it produces a UI/UX design whose value can be measured based on the measurement of user experience and the development of student learning motivation is also measured through four indicators, namely intrinsic motivation, identified regulation, external regulation, and amotivation. From these results, it can be concluded that the UI/UX design that has been developed produces an increased value and has a positive effect on the intrinsic motivation scale and identified regulation. However, the results of this UI/UX design have no influence on the scale of external regulation and motivation